Haunted texts : studies in Pre-Raphaelitism in honour of William E. Fredeman - Fredeman, William E. (William Evan), 1928-; Latham, David, 1950- (University of Toronto Press, 2003)
Begun by young rebels committed to revolutionizing the creative arts, Pre-Raphaelitism has moved from the margins of nineteenth-century art and literature to the vanguard of interdisciplinary studies. The term is now used to denote the Pre-Raphaelite, Aesthetic, and Decadent movements in art, culture, and literature, but it has remained as difficult to define as ever. Haunted Texts attempts to meet the challenge of defining and illustrating the full spectrum of Pre-Raphaelitism. Working with a diverse range of Pre-Raphaelite poetry, painting, decorative arts, book illustration, and political prose, the ten contributors to Haunted Texts pursue the critical strategies of such leading figures as Christina Rossetti and Dante Rossetti, William Morris and Oscar Wilde, Walter Pater, and Aubrey Beardsley. The essays consider the bibliocritical issues of archival research concerning the personal letters and diaries of the Rossetti family; the technological issues that challenge conventional methods of scholarship; the gender issues concerning constructions of identity derived from the changing conceptions of love, desire, anxiety, and brotherhood; and the interdisciplinary cultural issues that transgress the borders of high art and popular culture. Haunted Texts pays tribute to the scholarship of Professor William Fredeman who devoted much of his career since the 1950s to establishing a critical foundation that would enable future scholars to define their understanding of the complexity of Pre-Raphaelitism.